Cardiac‐specific ablation of glutaredoxin 3 leads to cardiac hypertrophy and heart failure. Issue 8 (29th April 2019) - Donelson, Jimmonique; Wang, Qiongling; Monroe, Tanner O.; Jiang, Xiqian; Zhou, Jianjie; Yu, Han; Mo, Qianxing; Sun, Qin; Marini, Juan C.; Wang, Xinquan; Nakata, Paul A.; Hirschi, Kendal D.; et al.
Abstract: Growing evidence suggests that redox‐sensitive proteins including glutaredoxins (Grxs) can protect cardiac muscle cells from oxidative stress‐induced damage. Mammalian Grx3 has been shown to be critical in regulating cellular redox states. However, how Grx3 affects cardiac function by modulating reactive oxygen species (ROS) signaling remains unknown. In this study, we found that the expression of Grx3 in the heart is decreased during aging. To assess the physiological role of Grx3 in the heart, we generated mice in which Grx3 was conditionally deleted in cardiomyocytes (Grx3 conditional knockout (CKO) mice). Grx3 CKO mice were viable and grew indistinguishably from their littermates at young age. No difference in cardiac function was found comparing Grx3 CKO mice and littermate controls at this age. However, by the age of 12 months, Grx3 CKO mice exhibited left ventricular hypertrophy with a significant decrease in ejection fraction and fractional shortening along with a significant increase of ROS production in cardiomyocytes compared to controls. Deletion of Grx3 also impaired Ca 2+ handling, caused enhanced sarcoplasmic reticulum (SR) calcium (Ca 2+ ) leak, and decreased SR Ca 2+ uptake. Furthermore, enhanced ROS production and alteration of Ca 2+ handling in cardiomyocytes occurred, prior to cardiac dysfunction in young mice. Therefore, our findings demonstrate that Grx3 is an important factor in regulating cardiac hypertrophy and heart failure by modulating both cellular redox homeostasis and Ca 2+ handling in the heart. Abstract : Disruption of Grx3 in the heart causes cardiac hypertrophy and heart failure in mice at a later age. Grx3 is a critical factor to control ROS production in cardiomyocytes. Deletion of Grx3 impaired Ca2 + handling in cardiomyocytes. Grx3 is an important negative regulator of cardiac hypertrophy and heart failure.